Quartz forming conditions in secant veins in granodiorites of the Andean intrusive complex of the Barchans Islands (Argentine Islands, West Antarctic) - Naumko, I.М.; Аrtemenko, G.V.; Bakhmutov, V.G.; Vovk, O.P.; Теlepko, L.F.; Sakhno, B.E. (Reports of the National Academy of Sciences of Ukraine, 2018)
It is established that the growth of quartz in veins in granodiorites of the Andean intrusive complex (the Barchans Islands, West Antarctic) happened in rock crystal-bearing veins of steep falling, in which the temperature difference necessary for the dissolution of massive quartz and crystallization of its transparent variety in the shape of perfectly cut crystals in central parts of secant veins was reached. The discovered enrichment of the fluid medium of the quartz crystallization with CO2, NaCl, and KCl indicates a carbonate-haloid composition of quartz-forming fluids, which favoured the formation of jewelry and technologically perfect crystals, possibly having piezoelectric properties similar to crystals of quartz both from rock-crystal-bearing veins of the Near-polar Ural and those synthesized under laboratory conditions. As a conclusion, the connection of quartz-forming fluids and the postmagmatic processes in a granodiorite intrusion is justified, and the view of investigated quartz veins as formations of post-tectonic hydrothermal stage is confirmed and expanded.